The Golden Age of Islamic Intellectuals and The Development of Science During The Abbasid Dynasty - Rusydi, Ibnu; Saepudin, Didin; Murodi, Murodi (Pascasarjana Universitas KH. Abdul Chalim, 2023)
This paper aims to examine the era of Islamic intellectual packaging during the reign of Caliph Harun al-Rashid during the Abbasid dynasty in Baghdad. History has recorded that during the reign of the Abbasid dynasty, Muslims were truly at the peak of their glory and led world civilization at that time. The reign of the Abbasid dynasty was a